Trouble River - Byars, Betsy Cromer; Negri, Rocco (New York, Viking Press, 1989)
When he builds his raft, a twelve-year-old boy never dreams that it will serve as the sole means of escape for himself and his grandmother when hostile Indians threaten their prairie cabin.
Keywords: Frontier and pioneer life